IMPROVING STUDENTS' ABILITY IN ANALYZING A WORK USING POPULAR MOVIE - SUSILOWATI, ENDANG; SAPTANTO, DESWANDITO DWI; ALKAROMAH, LATIFAH; BILA FAUZIYAH TAMAMI, SALSA (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2023)
Technological developments in learning process have provided flexibility for lecturer in carrying out lecture activities. Innovative and fun learning methods can certainly increase student interest in participating in the learning process. Movie as one of the audio-visual media that can improve understanding skills in interpreting the narrative presented in the storytelling. Movie also can improve listening and speaking skills, students can build an argument and statement about the story. This research is a form of integration between research whose output results will be integrated with the Movie Analysis course in the English Literature study program; Faculty of Economics, Law and Humanities; Universitas Ngudi Waluyo. Students of the English literature study program are required to be able to understand, interpret and retell the literary works or works of art they are studying. In the scope of this research, students will be given learning support materials in the form of a popular movie titled Avengers: End Game. The main focus of this research is to examine students' understanding through movie media. This assessment includes understanding the concept of storytelling, messages that appear in the storytelling and the ability to make a summary of the whole story in the movie. This implementation method is to use the discovery learning method, which is a learning method that encourages students to carry out investigations, find new things and build creativity in interpreting things by using their intuition, imagination and knowledge to find message behind the work. The method of carrying out this research was by distributing questionnaires and pre-test before carrying out the treatment process, then the process of implementing activities by watching the Avengers: End Game movie, and then distributing questionnaires and also post-test after the implementation of the activities was carried out. This research activity was carried out in the English Literature study program with students of the English Literature study program as the research subject. This study aims to improve students' ability to build understanding in interpreting the elements of the story. Through this research, students' analytical and interpretation skills on the elements of the story, namely themes, plots, characters and settings in a work, are increased.